Unraveling the tripartite interaction of volatile compounds of Streptomyces rochei with grain mold pathogens infecting sorghum - Sudha, A.; Durgadevi, D.; Archana, S.; Muthukumar, A.; Suthin Raj, T.; Nakkeeran, S.; Poczai, Peter; Nasif, Omaima; Ansari, Mohammad Javed; Sayyed, R. Z. (Frontiers in Microbiology, 2022)
Sorghum is a major grain crop for traditional meals, health drinks, and efficient fuel. However, its productivity, value, germination, and usability are affected due to grain mold being a severe problem in sorghum production systems, reducing the true of harvested grains for consumer use. The organic approach to the management of the disease is highly essential, and it will increase the demand among the consumer. The employment of VOCs (volatile organic compounds) producing biocontrol agents (BCA) is a significant integrated approach for the postharvest regulation of grain mold diseases. The Streptomyces rochei strain (ASP) has been reported to be a potential antagonist with the highest VOCs against many pathogens. The present study aimed to study the inhibitory effect of S. rochei against sorghum grain mold pathogens by dual culture technique and via the production of microbial volatile organic compounds (mVOCs). The mVOCs inhibited the mycelia growth of Fusarium moniliforme and Curvularia lunata by 63.75 and 68.52 percent, respectively. The mVOCs suppressed the mycelial growth and inhibited the production of spores by altering the structure of mycelium. About 45 mVOCs were profiled when Streptomyces rochei interacted with these two pathogens. In the present study, several compounds were up or down-regulated by S. rochei, including 2-methyl-1-butanol, methanoazulene, and cedrene. S. rochei emitted novel terpenoid compounds with peak areas, such as Myrcene (1.14), Cymene (6.41), and ç-Terpinene (7.32) upon interaction with F. moniliforme and C. lunata. Some of the compounds, viz., the peak intensity of furan 2 methyl (0.70), benzene (1.84), 1-butanol, 2-methyl-(8.25), and myrcene (1.12) increased during the interaction with F. moniliforme and C. lunata (6.60, 4.43, 18.67, 1.14). These metabolites were implicated in the sesquiterpenoid and alkane biosynthetic pathways and the oxalic acid degradation pathway. The present study shows how S. rochei exhibits hyperparasitism, competition, and antibiosis via mVOCs. In addition to their antimicrobial functions, these metabolites could also enhance plant growth.